2016
DOI: 10.2147/opth.s114306
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a trabecular microbypass stent with phacoemulsification in patients with open-angle glaucoma and cataract

Abstract: PurposeTo evaluate the safety and efficacy of the iStent trabecular microbypass stent in combination with cataract surgery in patients with open-angle glaucoma (OAG).MethodsRetrospective, consecutive case series from October 2012 to December 2015 with no exclusion criteria. The series comprised of 350 eyes with OAG and cataract. Data were collected both preoperatively and postoperatively at day 1 week 1, months 1, 3, 6, 12, 18, and 24. Data included intraocular pressure (IOP), number of glaucoma medications, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 17 publications
7
39
1
Order By: Relevance
“…The IOP reduction at M36 approached 5 mmHg (4.82) with 68% (n = 15) of eyes achieving an IOP ≤15 mmHg compared to 25% (n = 6) of eyes at baseline. Consistent with prior studies, this study also demonstrated a relationship between baseline IOP and reduction of pressure, which has been demonstrated both with phacoemulsification alone as well as prior MIGS studies. Eyes with baseline IOP ≥22 mmHg achieved a robust reduction in pressure at their last follow‐up with a mean of 9.3 mmHg, significantly greater than the IOP reduction observed in eyes with baseline pressure <18 mmHg.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The IOP reduction at M36 approached 5 mmHg (4.82) with 68% (n = 15) of eyes achieving an IOP ≤15 mmHg compared to 25% (n = 6) of eyes at baseline. Consistent with prior studies, this study also demonstrated a relationship between baseline IOP and reduction of pressure, which has been demonstrated both with phacoemulsification alone as well as prior MIGS studies. Eyes with baseline IOP ≥22 mmHg achieved a robust reduction in pressure at their last follow‐up with a mean of 9.3 mmHg, significantly greater than the IOP reduction observed in eyes with baseline pressure <18 mmHg.…”
Section: Discussionsupporting
confidence: 90%
“…Although this is not a true “off label” use of the device, the clinical trials leading to its approval did not include eyes with pigmentary or pseudoexfoliative glaucoma. In addition, while not directly comparable, the results of this study are comparable or superior to our published data in eyes with POAG and PXG . At M24 postoperative in those studies, the mean IOP reduction in the POAG and PXG eyes was 3.96 and 5.49 mmHg, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Studies also demonstrate that MIGS procedures are more effective in patients with higher baseline IOP. Accordingly, patients with lower baseline IOP, as in normal-tension glaucoma, are predisposed to smaller IOP reductions following MIGS procedures, with these results potentially insufficient to mitigate disease progression [52,53]. Although many therapeutic options for OAG exist, even patients with access to excellent care and cutting-edge treatments still progress to blindness.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…To date, this device has amassed a sizable longterm evidence base regarding its safety and performance in eyes with open-angle glaucoma, in settings both with and without cataract surgery. Most studies of the device have assessed outcomes in mild to moderate glaucoma [17][18][19][20][21][22][23][24][25][26][27], but other patient populations increasingly have been the subject of evaluation, such as pseudoexfoliative glaucoma, severe or refractory glaucoma, or newly diagnosed, treatment-naïve glaucoma [28][29][30][31][32][33]. Another growing and relevant area of investigation has been economics outcomes research [34][35][36][37][38][39], which consistently has shown favorable cost-effectiveness of the iStent in various healthcare models around the world.…”
Section: Introductionmentioning
confidence: 99%